An efficient method for identifying the chemical hazards of exception‐handling tasks and processes derived from abnormal process conditions. Issue 3 (28th December 2020) - Liaw, Horng‐Jang
Abstract: Hazards that result from inappropriate exception‐handling tasks and processes performed in response to abnormal process conditions are not easily identified or cannot be identified at all, using only traditional hazard identification methods, such as normal hazard and operability (HAZOP) studies, failure mode and effects analysis, what‐if analysis, procedural HAZOP, and job safety analysis. This study thus proposes an efficient chemical hazard‐based method for identifying such potential hazards. The method comprises a checklist for identifying intrinsic chemical hazards and the exception tasks and processes which may initiate such hazards and a worksheet for performing the chemical hazard assessment of the identified exception tasks and processes. The checklist provides management with a useful tool for identifying the exception tasks and processes which may result in chemical hazards. Meanwhile, the hazard assessment worksheet provides an effective tool for evaluating the potential chemical hazards of the identified exception‐handling tasks and processes, assessing the effectiveness of existing safeguards for preventing and reducing such hazards, and drawing up additional recommendations if required. The operation of the proposed method is demonstrated through two case studies.